2010
DOI: 10.1097/qad.0b013e32833e92d5
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic influenza A (H1N1) in HIV-1-infected patients

Abstract: HIV patients infected by the new influenza A pandemic (H1N1) virus behave similarly to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
5
3
Order By: Relevance
“…The retention of functions by the influenza-specific CD8 T cells during early SIV infection was somewhat surprising given the broad immunodeficiency induced by SIV. Indeed it was recently shown that some influenza strains can be more pathogenic in HIV-infected humans compared to HIV-negative humans, suggesting influenza-specific immunity is impaired during HIV infection [59]. On the other hand, in our study the SIV-specific CD8 T cells are actively responding to a persistent viral infection whereas the influenza-specific CD8 T cells are no longer responding to an antigenic challenge.…”
Section: Discussioncontrasting
confidence: 45%
“…The retention of functions by the influenza-specific CD8 T cells during early SIV infection was somewhat surprising given the broad immunodeficiency induced by SIV. Indeed it was recently shown that some influenza strains can be more pathogenic in HIV-infected humans compared to HIV-negative humans, suggesting influenza-specific immunity is impaired during HIV infection [59]. On the other hand, in our study the SIV-specific CD8 T cells are actively responding to a persistent viral infection whereas the influenza-specific CD8 T cells are no longer responding to an antigenic challenge.…”
Section: Discussioncontrasting
confidence: 45%
“…In fact, cases of severe complications with onset of pneumonia that led to hospitalization and that, in one case, required oxygen supplementation, were detected only in HIV-negative patients. This is in apparent contrast with previous findings, where no remarkable differences in clinical outcomes were observed in HIV-positive patients compared to HIV-negative subjects [18,19]. In a study by Peters et al, 911 subjects were analyzed in three separate cohorts, which included HIV+ patients with CD4 counts below 200, with half taking ART.…”
Section: Discussioncontrasting
confidence: 53%
“…Increased worldwide mortality was observed during the 2009 Influenza pandemics for especial groups of patients at higher risk, such as individuals immunocompromised [23,24] by cancer or transplantations [24]. Surprisingly, HIV-1-infected individuals presented a benign clinical outcome when infected by A(H1N1)pdm09 [25][26][27][28][29][30], unless when in AIDS [29]. Although Figure 5.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the increased mortality observed in immunocompromised individuals [23], such as cancer and transplanted patients [24], affected by the emergence of influenza A(H1N1)pdm09, HIV-1-infected individuals presented benign clinical outcomes [25][26][27][28][29][30]. For instance, Barchi et al found that the clinical outcome in HIV-1-infected individuals with A(H1N1)pdm09 infection was not different from that in immunocompetent patients [25], and Ormsby et al reported that only HIV-1-infected subjects that had progressed to the immune deficiency typical of AIDS presented an increased mortality by A(H1N1)pdm09 [29].…”
Section: Introductionmentioning
confidence: 99%